Muslim civic cultures and conflict resolution : the challenge of democratic federalism in Nigeria - Paden, John N. (Brookings Series on U.S. Policy Toward the Islamic World Ser., 2005)
"Examines how a diverse country with a significant Muslim population is working to make the transition to a democratic society, balancing rule-of-law concerns against rising communal tensions"--Provided by publisher